How does knee pain affect trunk and knee motion during badminton forehand lunges? - Huang, M.-T.; Lee, H.-H.; Lin, C.-F.; Tsai, Y.-J.; Liao, J.-C. (Journal of Sports Sciences, 2014)
Badminton requires extensive lower extremity movement and a precise coordination of the upper extremity and trunk movements. Accordingly, this study investigated motions of the trunk and the knee, control of dynamic stability and muscle activation patterns of individuals with and without knee pain. Seventeen participants with chronic knee pain and 17 healthy participants participated in the study and performed forehand forward and backward diagonal lunges. This study showed that those with knee pain exhibited smaller knee motions in frontal and horizontal planes during forward lunge but greater knee motions in sagittal plane during backward lunge. By contrast, in both tasks, the injured group showed a smaller value on the activation level of the paraspinal muscles in pre-impact phase, hip-shoulder separation angle, trunk forward inclination range and peak centre of mass (COM) velocity. Badminton players with knee pain adopt a more conservative movement pattern of the knee to minimise recurrence of knee pain. The healthy group exhibit better weight-shifting ability due to a greater control of the trunk and knee muscles. Training programmes for badminton players with knee pain should be designed to improve both the neuromuscular control and muscle strength of the core muscles and the knee extensor with focus on the backward lunge motion.